Podróż w czasie jako laboratorium narracji - Leś, Mariusz Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
Time travel is one of the most popular themes in science fiction. Usually it is discussed from a perspective of technological and scientific possibilities for the realization of fantastic visions. Researchers focus on logical paradoxes implied by traveling back in time. The author of this article, inspired by David Wittenberg’s Time Travel: The Popular Philosophy of Narrative, draws attention to metanarrative functions of time travel theme, which becomes a challenge for writers and narrative techniques.